Association Between Body Mass Index and Disability in Children With Charcot-Marie-Tooth Disease. (26th October 2021) - Donlevy, Gabrielle A.; Garnett, Sarah P.; Cornett, Kayla M.D.; McKay, Marnee J.; Baldwin, Jennifer N.; Shy, Rosemary R.; Yum, Sabrina W.; Estilow, Timothy; Moroni, Isabella; Foscan, Maria; Pagliano, Emanuela; Pareyson, Davide; et al.
Abstract : Background and Objectives: This study examined the association between body mass index (BMI) and disability in children with Charcot-Marie-Tooth disease (CMT). Methods: We conducted a cross-sectional analysis of 477 patients with CMT who were 3 to 20 years of age from the Inherited Neuropathy Consortium and 316 age- and sex-matched healthy children from the 1, 000 Norms Project. BMI was categorized according to the International Obesity Task Force (IOTF) criteria, and BMI categorization was compared with healthy children. IOTF categories (adult equivalent BMI cut points) were severely underweight (BMI <17 kg/m 2 ), underweight (BMI ≥17–<18.5 kg/m 2 ), healthy weight (BMI ≥18.5–<25 kg/m 2 ), overweight (BMI ≥25–<30 kg/m 2 ), and obese (BMI ≥30 kg/m 2 ). Scores on the 0 to 44–point CMT Pediatric Scale (CMTPedS), a well-validated measure of disability, were examined in relation to BMI. Results: There was a higher proportion of children with CMT categorized as severely underweight (5.7% vs 0.3%), underweight (10.3% vs 5.1%), and obese (7.3% vs 3.8%) ( p < 0.05). Fewer children with CMT were categorized as healthy weight (61.8% vs 74.4%) ( p < 0.05), and the proportion of overweight (14.9% vs 16.5%) between groups was similar. CMTPedS scores (mean ± SD) for weight categories were as follows: severely underweight 27 ± 9, underweight 20 ± 8, healthy weight 17 ± 9, overweight 17 ± 9, and obese 22 ± 10. Compared to children with a healthy weight with CMT, being severely underweight was associated with being more disabled ( p < 0.001), as was being obese ( p = 0.015). Discussion: The proportion of children with CMT who are underweight or obese is higher compared to age- and sex-matched healthy children. In children with CMT, being underweight or obese is associated with greater disability, when compared to children with CMT of healthy weight.